The Impact of Seaport Competition on Technical Efficiency: Simar–Wilson Analysis of European Container Ports - Kammoun, Rabeb; Abdennadher, Chokri (Transactions on Maritime Science, 2023)
This paper examines the effects of environmental factors (port-city GDP, population size, connectivity to hinterland, draught level and distance from the closest port Hub) and competition on the efficiency of a number of North and South European seaports. For this purpose, a bootstrap data envelopment analysis truncated regression approach was applied to 35 container ports, in the 2004 - 2018 period. Research findings indicate that the connectivity of a port’s country and draught level have a positive impact on the efficiency of both Northern and Southern European seaports. In addition, our results revealed that the efficiency of Southern European seaports tends to increase with competition intensity, whereas that of Northern European seaports seems to decrease with intensified competition, due to investment discrepancies, necessary for attracting a wider range of customers.